Gd3+-DTPA-bis (N-methylamine) – Anionic Linear Globular Dendrimer-G1; A More Efficient MRI Contrast Media - Ghalandarlaki, N.; Mohammadi, T. D.; Agha Babaei, R.; Tabasi, M. A.; Keyhanvar, P.; Mehravi, B.; Yaghmaei, P.; Cohan, R. A.; Ardestani, M. S. (Drug Research, 2014)
By advancing of molecular imaging techniques, magnetic resonance imaging (MRI) is becoming an increasingly important tool in early diagnosis. Researchers have found new ways to increase contrast of MRI images.Therefore some types of drug known as contrast media are produced. Contrast media improve the visibility of internal body structures in MRI images. Gadodiamide (Omniscan®) is one of these contrast media which is produced commercially and used clinically. In this study Gadodiamide was first synthesized and then qualitative and quantitative methods were carried out to ensure the proper synthesis of this drug then to increase the efficiency of this contrast medium use dendrimer that is one kind of nano particle. This dendrimer has a polyethylene glycol (PEG) core and citric acid branches. After dendrimer attached to Gadodiamide to ensure the proper efficient connection between them the stability studies were carried out and cytotoxicity of the drug was evaluated. Finally, after ensuring the non-toxicity of the drug, in vivo studies (injected into mice) MR imaging was performed to examine the impact of synthesis drug on the resolution of image.The result obtained from this study demonstrated that the attachment of Gadodiamide to dendrimer reduces its cytotoxicity and also improved resolution of image. Also the new contrast media (Gd3+-DTPA- bis [N-methylamine] – Dendrimer) – unlike Omniscan® – is biodegradable and able to enter the HEPG2 cell line. The results confirm the hypothesis that using dendrimer to synthesize this new nano contrast medium increases its effectiveness.
Keywords: cancer diagnosis; molecular imaging; MRI; contrast media; omniscan; dendrimer; gadodiamide